SINERGI GURU PAI DAN PENGURUS ROHIS DALAM MENINGKATKAN PERILAKU KETAATANBERAGAMA SISWA DI SMP 3 KENDARI - Sari, Nur Azizah Wulan; Safrudin, Moh.; Erdiyanti, Erdiyanti (Dirasah: Jurnal Pendidikan Islam, 2024)
The objectives of this study are, 1) to know the condition of students’ religious obedience behavior at SMP Negeri 3 Kendari, 2) to know the synergy form of PAI Teacher and ROHIS Management in Improving Students’ Religious Obedience Behavior at SMP Negeri 3 Kendari, 3) to know the supporting and Inhibiting factors in building the synergy of PAI Teachers and ROHIS administrators in improving the religious obedience behavior of SMP Negeri 3 Kendari students. The type of research used is descriptive research with a qualitative approach. Data collection techniques using observation, interviews and documentation. Informants in this study are curriculum, PAI teachers and students. Data analysis using descriptive qualitative. The results of this study are, 1) the condition of students’ religious obedience behavior at SMP Negeri 3 Kendari, namely respecting teachers and guests who are visiting, carrying out dhuha prayers at rest hours and dhuhur prayers in congregation, carrying out infaq and reciting/yasinan every Friday morning, 2) the synergy carried out by PAI Teachers and ROHIS administrators is by communicating well, sharing roles in religious activities.3) the supporting factors are students who have great enthusiasm for participating in activities with school facilities provided and very adequate and support from teachers during the learning process, while the inhibiting factors that occur are family factors, disruption of student health and the biggest factor is the individual students themselves.AbstrakTujuan penelitian ini adalah, 1) mengetahui kondisi perilaku ketaatan bergama siswa di SMP Negeri 3 Kendari, 2) mengetahui bentuk sinergi Guru PAI dan Pengurus ROHIS dalam Meningkatkan Perilaku Ketaatan Beragama Siswa di SMP Negeri 3 Kendari, 3) mengetahui faktor pendukung dan penghambat dalam membangun sinergi Guru PAI dan pengurus ROHIS dalam meningkatkan perilaku ketaatan beragama siswa SMP Negeri 3 Kendari. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Informan dalam penelitian ini yaitu kurikulum, Guru PAI dan peserta didik. Analisis data menggunakan deskriptif kualitatif. Hasil dari penelitian ini yaitu, 1) kondisi perilaku ketaatan beragama siswa di SMP Negeri 3 Kendari yaitu menghormati Guru serta tamu yang sedang berkunjung, melaksanakan sholat dhuha di jam istrahat dan sholat dzuhur secara berjama’ah, melaksanakan infaq dan mengaji/yasinan disetiap jum’at pagi, 2) sinergi yang dilakukan Guru PAI dan pengurus ROHIS yaitu dengan melakukan komunikasi yang baik, berbagi peran dalam kegiatan keagamaan 3) faktor pendukungnya adalah siswa-siswi yang memiliki semangat besar untuk mengikuti kegiatan dengan fasilitas sekolah yang disediakan dan sangat memadai serta dukungan dari Guru-guru selama mengikuti proses pembelajaran, sedangkan faktor penghambat yang terjadi adalah adanya faktor dari keluarga, terganggunya kesehatan siswa serta faktor terbesarnya adalah dari individu siswa itu sendiri.